Blood pressure in a national birth cohort at the age of 36 related to social and familial factors, smoking, and body mass. Issue 6508 (30th November 1985) - Wadsworth, M E; Cripps, H A; Midwinter, R E; Colley, J R
Abstract : Blood pressure was measured in a birth cohort of 5362 subjects at the age of 36. The prevalence of hypertension in men (blood pressure greater than 140/90 mm Hg) was almost twice that in women, although women received treatment more often. Deaths of fathers of subjects from hypertensive and ischaemic heart disease were associated with significantly higher mean systolic and diastolic pressures in both sexes. Cigarette smoking was not strongly associated with blood pressure in men and not associated at all in women. Of the social factors, low social class of family of origin was associated with high blood pressure in both sexes; but the strongest association was with current body mass, and birth weight also contributed. Differences in blood pressures between the sexes may have been related to protective biological factors, such as endogenous sex hormones, in women and also to differences in types of employment, smoking habits, and body mass. Differences in blood pressures related to the social class of family of origin may reflect long term influences of class differences on diet, exercise, and educational achievement. The importance of measuring secular trends in obesity and blood pressures is emphasised.